2008
DOI: 10.2478/s11536-008-0069-z
|View full text |Cite
|
Sign up to set email alerts
|

Sedation for middle ear surgery: prospective clinical trial comparing propofol and midazolam

Abstract: AbstractDuring middle-ear-surgery under local anaesthesia (MES-LA), patients report hearing noises, feeling anxious, and experiencing earache. In a prospective randomized clinical trial, we compared propofol and midazolam for sedation in 68 patients scheduled for MES-LA. The starting dose of propofol was 1 to 1.5 mg per kilogram intravenously, followed by 1 to 2 mg per kilogram per hour given by infusion. The starting dose of midazolam was 0.02 to 0.05 mg per kilogram intraveno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
1
13
1
Order By: Relevance
“…Previous studies had compared the administration of Propofol and Midazolam in middle ear procedures. In his study Benedik J et al [8] reported that Propofol is more appropriate than Midazolam to make sedation in patients undergoing middle ear surgery, but in our study we recorded higher depth of anesthesia with Midazolam than Propofol, which was not statistically significant. In previous studies it has been shown that Propofol -Remifentanil is an appropriate method in ear surgery procedure because of its rapid recovery, creating intraoperative well condition and reducing post operation nausea and vomiting [1,2].…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Previous studies had compared the administration of Propofol and Midazolam in middle ear procedures. In his study Benedik J et al [8] reported that Propofol is more appropriate than Midazolam to make sedation in patients undergoing middle ear surgery, but in our study we recorded higher depth of anesthesia with Midazolam than Propofol, which was not statistically significant. In previous studies it has been shown that Propofol -Remifentanil is an appropriate method in ear surgery procedure because of its rapid recovery, creating intraoperative well condition and reducing post operation nausea and vomiting [1,2].…”
Section: Discussioncontrasting
confidence: 82%
“…The procedures related to ear are very sensitive to stimulations particularly during the surgery, so creating a setting with minimal movements is inevitable which requires relatively deep anesthesia. Various sedative and hypnotic drugs have been used in numerous studies for middle ear surgery to facilitate the operation till now [1,2,[6][7][8][9]. In recent years, it has been shown that intravenous administration of Propofol in middle ear surgery has led to better condition during operation [1].…”
Section: Discussionmentioning
confidence: 99%
“…12 Similarly, Benedik et al compared propofol with midazolam infusion for sedation in middle ear surgeries which showed better sedation score with propofol. 13 However, we did not use any sedation score like Ramsay sedation score or Bispectral index monitoring to titrate the drug like in other studies. 9,12,13 We used mixture of injection 2% lignocaine with adrenaline 1:80000 and 0.5% bupivacaine 1:80000 in the volume of 12-16 ml.…”
Section: Methodsmentioning
confidence: 99%
“…13 However, we did not use any sedation score like Ramsay sedation score or Bispectral index monitoring to titrate the drug like in other studies. 9,12,13 We used mixture of injection 2% lignocaine with adrenaline 1:80000 and 0.5% bupivacaine 1:80000 in the volume of 12-16 ml. In some studies they have used injection lignocaine 2% with adrenaline 1:200,000.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation